Investigations on the Structural and Mechanical Properties of Polyurethane Resins Based on Cu(II)phthalocyanines - Tamer E. Youssef; Hamad Al-Turaif; AbdulAziz A. Wazzan (International Journal of Polymer Science)
This work report was reported on the effect of the addition of organic filler, that is, 2(3),9(10),16(17),23(24)-octahydroxycopper(II)phthalocyanine [(OH)8CuPc] (3), on the thermal, tensile, and morphological properties of a polyurethane matrix. The mechanical and dynamic mechanical thermal tests together with microstructural characterization of CuPc/PU composites were performed. The three PU composite films containing up to 1, 15, and 30 wt% of CuPc have different behaviors in terms of their morphological issues, thermal properties, and tensile behavior in comparison with the PU film as the reference material. Very high elongations at break from 910% to 1230%, as well as high tensile strengths, illustrate excellent ultimate tensile properties of the prepared samples. The best mechanical and thermomechanical properties were found for the sample filled with 30 wt% of CuPc.